2019
DOI: 10.1039/c9na00471h
|View full text |Cite
|
Sign up to set email alerts
|

High-performance ultra-violet phototransistors based on CVT-grown high quality SnS2flakes

Abstract: High-performance UV photodetectors established on CVT-grown SnS2flakes provide an efficient way to choose 2D crystals with an optimal thickness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 67 publications
1
33
0
Order By: Relevance
“…As far as we know, this excellent performance is the highest ever recorded by all the numerous reported SnS 2 devices. [ 9,10,20,38 ] However, we also observed that the two quantities' values ( R λ and EQE) slightly changed as the light power increases, which could be due to the absorbance saturation attained by the photodetector.…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…As far as we know, this excellent performance is the highest ever recorded by all the numerous reported SnS 2 devices. [ 9,10,20,38 ] However, we also observed that the two quantities' values ( R λ and EQE) slightly changed as the light power increases, which could be due to the absorbance saturation attained by the photodetector.…”
Section: Resultsmentioning
confidence: 83%
“…First, from the extracted electrical measurements, the back‐gate FET device exhibits an intrinsic n‐type semiconducting response that is compatible with earlier investigated SnS 2 devices. [ 10,38 ] Here, we calculated the field‐effect mobilities for the original and O 2 ‐plasma‐treated devices, which are 2.71 and 3.10 cm 2 V −1 s −1 , respectively, using; μe=dId LdVgWCiVd, ( L is the length and W is the width of the device, and C i is equivalent 11.6 nF cm −2 , which is the capacitance per unit area for 300 nm SiO 2 substrate used). [ 21 ] In an ambient condition, the extracted carrier mobility from the treated SnS 2 FET is one of the highest reported so far.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the quantum confinement effect and the strong interlayer coupling effect, two-dimensional (2D) layered materials such as transition metal dichalcogenides (TMDs) (Molybdenum disulfide, Tungsten disulfide, etc) have attracted tremendous attentions with unique thickness dependent and strain-tunable physical properties [1][2][3][4][5][6][7]. In recent years, beyond the discovery of graphene, other novel monoelemental 2D layered materials such as black phosphorus (BP), arsenic (As), bismuth (Bi), tellurium (Te), antimonene (Sb), which show tunable band gap, theoretical high carrier mobility, atomically flat surface, strong spin orbital torque, high light absorption efficiency, have been experimentally explored as promising candidates for applications in filed effect transistors (FETs), spintronics and photodetectors (PDs) [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%